Neutrophil extracellular traps regulating tumorimmunity in hepatocellular carcinoma - Zhu, Weixiong; Fan, Chuanlei; Dong, Shi; Li, Xin; Chen, Haofei; Zhou, Wence (Frontiers in Immunology, 2023)
As a component of the innate immune system, there is emerging evidence to suggest that neutrophils may play a critical role in the initiation and progression of hepatocellular carcinoma (HCC). Neutrophil extracellular traps (NETs) are web-like chromatin structures that protrude from the membranes during neutrophil activation. Recent research has shown that NETs, which are at the forefront of the renewed interest in neutrophil studies, are increasingly intertwined with HCC. By exploring the mechanisms of NETs in HCC, we aim to improve our understanding of the role of NETs and gain deeper insights into neutrophil biology. Therefore, this article provides a summary of key findings and discusses the emerging field of NETs in HCC.